Search for the Standard Model Higgs boson in e+e− collisions at √s up to 202 GeV - Dova, María Teresa (2001)
The Standard Model Higgs boson is searched for in 233.2 pb−1 of data collected by the L3 detector at centre of mass energies from 192 GeV to 202 GeV. These data are consistent with the expectations of Standard Model processes and no evidence of a Higgs signal is observed. A lower limit on the mass of the Standard Model Higgs boson of 107.0 GeV is set at the 95% confidence level.